A government farm bull cutting lawn, Queen’s Park Savannah, Trinidad, B.W.I. - (:unkn) unknown (My University, 2009)
A labourer using a bull to cut the grass in the Queen’s Park Savannah. Postcard number c 27275.
Colour: Black and white; Other: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Draft animals--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--Port of Spain; Savannas--Trinidad and Tobago; Lawn mowers--Trinidad and Tobago; Lawn care industry--Trinidad and Tobago; Queen’s Park Savannah